Obtaining design information from full-scale structures - Blight, Geoffrey Eustice (Department of Civil Engineering, 2024)
It is believed that this is the first time, or one of the few occasions on which the aims and objectives of field observation and measurement have been analysed to establish principles that should be followed in future exercises of this type. 1.2 1.3 Tropical residual soils display certain differences in their behaviour from transported soils. This paper shows that provided these differences are recognized, the behaviour of tropical soils under load can be rationally predicted. While the broad behaviour of hydraulic fill soil structures is well understood, certain aspects of the detailed behaviour of hydraulic fill are less well appreciated. A number of these aspects are discussed in the paper in relation to several applications of hydraulic filling.